FADING THE EFFECTS OF CORONAVIRUS WITH MONETARY POLICY - MALATA, Alain K.; PINSHI, Christian P. (Theoretical and Practical Research in Economic Fields; Vol 11 No 2 (2020): TPREF, Volume XI, Issue 2(22), Winter 2020, 2020)
The Central Bank of Congo (BCC) reduced the policy rate in response to the uncertain effects of the coronavirus. The impact of the pandemic on the economy is still uncertain and depends on many factors. Using the Bayesian technique of the VAR model we notice that cutting the policy rate would not help the economy to cope with the consequences of COVID-19, we should rethink other tactics and strategies, such as a good communication strategy and / or try unconventional monetary policy measures. However, coordination with fiscal policy is a driver key in blurring the effects of the coronavirus crisis [1] .   [1] Opinions expressed on this paper do not necessarily reflect the views of the Central Bank of Congo.